Revision of Xyris L. (Xyridaceae) in Thailand - Phonsena, Phongsak; Chantaranothai, Pranom; Meesawat, Amornrat (Thai Forest Bulletin (Botany), 2014)
Xyridaceae (with only one genus, Xyris L.) was treated for the Flora of Thailand by Hansen in 1987 with 11 species. Through extended collection, with observations in the fi eld and new methodologies in particular in specimens from north-eastern Thailand, at present 17 indigenous species have been recognized, including four new species and two new records for Thailand. An updated key to the species is provided. Lectotypes have been designated for all names as necessary. All species are described and illustrated.